Are two children at once better than one? Risk analysis of twin pregnancies and births after assisted reproduction. (September 2021) - Goeckenjan, Maren; Madej, Daria; Klimova, Anna; Wimberger, Pauline; Birdir, Cahit; Glaß, Katrin
Abstract: Objectives: Pregnancies and births following assisted reproductive treatment (ART) are related to an increased risk for adverse perinatal outcomes. The aim of this retrospective cohort study at a University Hospital with a tertiary perinatal center was the combined risk analysis of singleton and twin pregnancies after ART in comparison to spontaneously conceived pregnancies. Study design: Maternal and fetal risks were analyzed in subgroups after spontaneous conception ( N = 14, 233) and ART (N = 785) during the 6-year study period from 2014 to 2019. Odds ratios for perinatal risks between the groups were calculated and adjusted for maternal age and gestational week at birth using a matched control analysis. Subgroups of preterm delivery were compared. Results: The overall maternofetal risks after ART are higher than after spontaneous conception. Maternal risks after ART are mainly related to higher maternal age (p < 0.001). Preterm delivery and neonatal complications are more frequent in twins than in singletons (p < 0.001), but no statistically significant differences were seen in comparison in the subgroup of twins due to conception. Higher maternal age and body mass index did not increase the risk of preterm birth in twin pregnancies. Conclusions: Maternal risks in pregnancies after ART are mainly influenced by maternal age. The strongest risk factor in ART pregnancies is a multiple pregnancy. Every 5th pregnancy after ART was a twin pregnancy with higher risks for preterm delivery, maternal hospitalization and adverse neonatal outcome (p < 0.001). Advanced maternal age in ART cannot be altered, but twin pregnancies can be actively avoided using the single embryo transfer strategy.